Characterization of a neutron irradiation facility using Monte Carlo simulations and activation dosimetry - Pantousa, Sofia; Vasilopoulou, Theodora; Savva, Marilia; Kokkoris, Michael; Vlastou, Rosa; Stamatelatos, Ion Evangelos (HNPS Advances in Nuclear Physics, 2020)
In the present work, the fluence rate at the sample irradiation positions for a neutron irradiation system based on two 239Pu(α, n)9Be radionuclide neutron sources of nominal total activity of 444 GBq was derived. The measurements were performed using a set of activation dosimetry foils comprising gold, indium, iron, zinc, cobalt and aluminum and a high purity germanium based gamma spectrometry system. The measurements were supported by Monte Carlo simulations performed using the MCNP6 code. The results of the study showed that the neutron emission rate of the sources was (3.41 ± 0.53)×107 n/s and the neutron fluence rate at the central sample position was (5.70 ± 0.80)×105 cm-2s-1. Although radionuclide neutron sources cannot achieve the high fluence rates encountered in nuclear research reactor and accelerator facilities, they provide a simple and cost effective method for fast neutron irradiation of samples under constant neutron fluence rate conditions. The system will be used for neutron dosimetry and material irradiation studies.